Experiences of Educators in Teaching Listening Skills: A Phenomenological Study on a Rural Public School - Agon, Rodolfo (International Journal of Arts, Sciences and Education, 2025)
Purpose: This study aims to examine and understand the experiences of teachers in teaching listening skills to students in a rural public school. A phenomenological approach was used as a method to describe and share their personal experiences, challenges, and strategies used to improve students’ listening skills. Methodology: Through interviews and in-depth data analysis, various issues were identified, such as the lack of knowledge about strategies, limited teacher training, and environmental factors that may affect the effective teaching of listening. Significance: Effective strategies were discovered, including the use of modern technology, integration of interactive activities, and providing contextualized learning experiences. The study shows that it is essential to provide adequate support and training to teachers to enhance their ability to teach listening effectively. Importance: This highlights the need to enrich teaching methods to improve the listening skills of students in rural public schools.